Ischemic stroke in coronavirus disease 19 (COVID-19) positive patient: a case report - Rosa De Lima Renita Sanyasi; Esdras Ardi Pramudita (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2020)
A new coronavirus disease called COVID-19 was declared by World Health Organization (WHO). The COVID-19 may complicated into many other conditions, including neurologic. One among this neurologic complication is stroke. This paper aimed to report a case of ischemic stroke in COVID-19 positive patient in Yogyakarta, Indonesia. A male patient, 42 years old, came to emergency department with weakness in his right arm for two days as his main complain. He also had face drop on the right side, cough, and shortness of breath. He had a history of hyperthyroid and type II diabetes mellitus. The brain CT Scan showed a lacunar infarct in the left lentiform nucleus. Patient had nasopharynx and oropharynx swab to be checked for the presence of COVID-19 and the result was positive.The pathophysiology of stroke in COVID-19 include the hyperactivation of inflammatory factors that causes a fatal inflammatory storm. It also cause a damage of coagulation system which causing the D-dimer and platelet abnormalities, hypercoagulability from critical illness and cardioembolism from virus-related cardiac injury. Moreover, COVID-19 may cause a direct role in viral infection in central nervous system. In conclusion, ischemic stroke can be present along with COVID-19.